The intention to use mobile banking: Further evidence from Saudi Arabia - I. M. Al-Jabri (South African Journal of Business Management, 2015)
The purpose of this research paper is to develop and examine a research model to understand the factors that affect the intention to use mobile banking services in Saudi Arabia. Based on a paper-based survey of 253 respondents, the studyutilized a Partial Least Squares (PLS) to empirically test the model. The results indicated strong support for the validity of proposed model with 66,7% of the variance in intention to use mobile banking. The results also indicated thatcompatibility was the strongest facilitator of intention while perceived risk was a barrier to the intention to use mobile banking. Trust had strong negative relationship with perceived risk, indicating that trust may alleviate the risk barrier, which could influence intention to use mobile banking. Contrary to previous research, perceived usefulness and perceived ease of use did not have significant effect on intention to use mobile banking. The implications of the findings were discussed and suggestions for future research were presented.
Keywords: 650